Neuromechanical evidence of improved neuromuscular control around knee joint in volleyball players - Masci, I.; Vannozzi, G.; Gizzi, L.; Bellotti, P.; Felici, F. (European Journal of Applied Physiology, 2010)
The aim of the present work was to verify that skilled volleyball players present specific adaptations in both neuromuscular control and movement biomechanics, showing an improved neuromuscular control around the knee joint than in non-jumper athletes. Seven male volleyball players and seven male non-jumper athletes were recruited for this study. The following tests were performed in a random order: single countermovement jump (CMJ), single squat jump. At the end of the series, subjects performed a repetitive CMJ test. Electromyographic signals were recorded from vastus lateralis and biceps femoris muscles on both sides. Ground reaction forces and moments were measured with a force plate. Volleyball athletes performed better in all tests and were more resistant to fatigue than non-jumper athletes. Furthermore, volleyball athletes showed a reduced co-activation of knee flexor/extensor muscles. The present results seem to stand for a neural adaptation of the motor control scheme to training.